2006
DOI: 10.1002/elps.200500875
|View full text |Cite
|
Sign up to set email alerts
|

Scanning copy number and gene expression on the 16p13.3‐13.2 chromosomal region by the systematic multiplex polymerase chain reaction and reverse transcription‐polymerase chain reaction methods

Abstract: We developed the systematic multiplex reverse transcription-PCR (SM RT-PCR) method that is distinguishable from other multiplex RT-PCR methods by optimized PCR conditions allowing amplification of sequences that fall within a single exon of genes of similar band intensity using genomic DNA template as a calibration standard. Using an SM RT-PCR system of proto-oncogenes and tumor suppressor genes, we previously showed that the SM RT-PCR system, which was developed for cDNA expression analysis, could also be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Using a model SM (RT-)PCR system that contained genes from autosomes and the X chromosome, we previously demonstrated that less than a twofold difference in copy number could be detected by SM PCR [11]. In the present study we applied SM PCR and SM RT-PCR to examine the changes in copy number and expression of more than a hundred of genes in breast and prostate tumors and cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Using a model SM (RT-)PCR system that contained genes from autosomes and the X chromosome, we previously demonstrated that less than a twofold difference in copy number could be detected by SM PCR [11]. In the present study we applied SM PCR and SM RT-PCR to examine the changes in copy number and expression of more than a hundred of genes in breast and prostate tumors and cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…Using control genomic DNA template, the optimal primer concentrations were determined to unify band intensity as previously described [8][9][10][11]. Out of 140 genes on the chromosomal region of 18q21-qter, 13 genes failed to amplify specifically and were excluded from the system.…”
Section: Sm Pcr and Sm Rt-pcr Analyses Of The Genes On The Chromosomamentioning
confidence: 99%
See 2 more Smart Citations
“…We prepared cDNA by reverse-transcription using oligo dT primers and the Advantage RT-for-PCR Kit (BD Biosciences-Clontech). We followed the SM RT-PCR experimental protocols described previously [29], [50], [51], [52]. Complementary DNA samples were used as templates to examine gene expression.…”
Section: Methodsmentioning
confidence: 99%